Digitalisasi Pelayanan Publik Fisip UNNES Sebagai Strategi Reformasi Birokrasi Menuju Kampus Bersih Dan Melayani - Natal Kristiono; Rudi Salam; Indri Astuti; Hanik Latifah; Amalia Adya P; Sa’ya Rosyada Al Firdaus; Meike Dwi Novita; Ananda Aurora Khaerunisa (Departement of Mathematics Education, 2024)
Eradicating corruption in public services requires cooperation and participation from all parties, especially from the government, society and the private sector. This can ensure that the public services provided are of quality, transparency and integrity. The governement holds a huge burden in eradicating corruption and providing public services. The governmenent has a responsibility to ensure that the public services provided to the community are not affected by corrupt practices. One effort to eradicate corruption is to implement digitalization of public services. Digitalization of public services is a step in the use of information and communication technology to improvr public services. This article will discuss the digitalization of public services in eradicating corruption as a bureaucratic reform strategy with the scope of implementing digitalization of public services, effort to eradicate corruption, obstacles to implementing digitalization of public services, and optimizing digitalization of public services. By using socio-legal reseach methods in this article, it can be concluded that digitalization can reduce opportunities for corruption through reducing direct contact, increasting the efficiency and effectiveness of public services, increasing the accessibility and transparency of public information, as well as increasing public participation in decision making regarding public services. Therefore, digitalization of public services needs to countinue to be improved and developed as a way to grow public services that are open and can be responsible in carrying out their duties.